Predictive value of left atrial appendage lobes on left atrial thrombus or spontaneous echo contrast in patients with non-valvular atrial fibrillation - Wang, Fan (BMC Cardiovasc Disord, 2018)
BACKGROUND: Left atrial appendage morphology has been proved to be an important predictor of left atrial thrombus (LAT) and left atrial spontaneous echo contrast (LASEC) and stroke in patients with non-valvular atrial fibrillation (NVAF). However, the relation between left atrial appendage (LAA) lobes and LAT or LASEC is still unknown. The aim of this study is to investigate the correlation between the number of left atrial appendage lobes and LAT/LASEC in patients with NVAF. METHODS: This monocentric cross-sectional study enrolled 472 consecutive patients with non-valvular atrial fibrillation, who had transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) prior to cardioversion or left atrial appendage closure (LAAC) from July 2009 to August 2015 in department of cardiology of Shanghai Tenth People’s Hospital. Patients who had significant mitral or aortic valve disease, previous cardiac valvular surgery and other complicated cardiac diseases were excluded. Individuals were divided into two groups:the LAT/LASEC group (16.95%), which comprised patients with LAT or LASEC, as confirmed by TEE; and a negative control group (83.05%).Baseline overall group characterization with demographic, clinical, laboratory data and echocardiographic parameters, alongside with information on medication was obtained for all patients. Subgroup analysis with line chart was applied for exploring the association between LAA lobes and LAT/LAESC. Receptor-operating curves (ROC) were used to test the value of LA anteroposterior diameter detected by different echocardiography methods predicting LAT or LASEC. Multivariable logistic regression analysis was used to investigate independent predictors of LAT/LASEC. RESULTS: Among 472 patients, 23 (4.87%) had LA/LAA thrombus and 57 (12.1%) had LA spontaneous echo contrast. Compared to the negative group, patients in LAT/LASEC group had higher CHA(2)DS(2)-VASc score (3.79 ± 1.75 vs 2.65 ± 1.76, p < 0.001), larger LAD (measured by TTE, 48.1 ± 7.7 vs 44.6 ± 6.5, P < 0.001; measured by TEE, 52.2 ± 6.2 vs 46.7 ± 7.1, P < 0.001), lower left upper pulmonary venous flow velocity (LUPVFV) (0.54 ± 0.17 m/s vs 0.67 ± 0.26 m/s, CI 95% 0.05–0.22, P = 0.003), more left atrial appendage lobes (1.67 ± 0.77 vs 1.25 ± 0.50, p < 0.001). There was a good discriminative capacity for LAD detected by TTE (area under the curve (AUC), 0.67, CI 95% 0.61–0.73, p < 0.001) and LAD detected by TEE (AUC, 0.73, CI 95% 0.67–0.79, p < 0.001). The subgroup analysis based on gender and different LAA lobes yielded similar results (male group: p < 0.001;female group: p = 0.004) that the number of LAA lobes were significantly associated with LA thrombus or SEC. In multivariable logistic regression analysis, both the number of LAA lobes (odds ratio: 2.37; CI 95% 1.37–4.09; p = 0.002) and the persistent AF (odds ratio: 3.57; CI 95% 1.68–7.57; p = 0.001) provided independent and incremental predictive value beyond CHA(2)DS(2)-VASc score. CONCLUSION: The number of LAA lobes is an independent risk factor and has a moderate predictive value for LAT/LASEC among NVAF patients in China.